(untitled) (Development Service Industry Management, 2025)
In modern conditions of globalization, digitalization, and increasing competitive pressure, strategic innovation management has become a decisive factor in ensuring the sustainable development of business entities. Innovations play not only the role of an "engine" of socio-economic growth but also serve as a tool for adapting to dynamic changes in the external competitive environment. Effective strategic innovation management enables the formation of competitive advantages, quick adaptation to changes, reorientation to new markets, and increased efficiency in using both internal and external resources. The purpose of the article is to form the theoretical foundation for the intellectual and strategic management of the innovativeness of business entities under uncertainty. The relevance of this management lies in the creation of a dynamic system that ensures the timely determination of innovation missions, goals, and prospects, as well as the development and implementation of innovation-oriented plans. This contributes to increasing the innovation potential of business entities, forming sustainable competitive advantages, and ensuring effective functioning in dynamic markets. The concepts of "strategy" and "management" are key in the mechanisms for the development of business entities. Strategy defines directions and long-term goals, while the management system ensures planning, organization, motivation, and control for their effective implementation. The innovation process is a core element of socio-economic relations and represents creative changes aimed at developing management systems. In modern conditions, there is a shift from viewing innovations as results to analyzing the ability of business entities to generate and adapt to current challenges. The article focuses on forming the theoretical basis for "intellectual-strategic management of innovativeness," which combines strategic planning, management functions, and innovative solutions. This concept is crucial for enhancing the competitiveness of business entities in a dynamically changing environment. The study analyzes the functions of management and their role in strategic innovation management. It explores the types of business strategies and the principles of strategic management of innovations, which contribute to the adaptability of business entities to internal and external changes. The theoretical foundation of intellectual-strategic management of innovativeness has been created, forming the basis for the successful development of business entities in response to changing internal and external factors.